The Production of Race, Locality, and State: An Anthropology - Sider, Gerald (Anthropologica, 2022)
This paper is an examination of some of the causes and consequences of state-managed processes that make very large numbers of people useless in their own localities. Examples are drawn from the displacement of African American workers in North Carolina by undocumented Central Americans, and the massive layoffs in Newfoundland—the largest in Canadian history—following the commercial extinction of Newfoundland and Labrador's cod fish and the closure of the fishery in 1992. This essay focusses on both the contradictions of citizenship and on the consequences of exporting people for work elsewhere. New ways of analyzing rupture and chaos are suggested, as are some implications for progressive political strategies.